2017
DOI: 10.1210/en.2017-00486
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Manipulations That Induce Ketosis Activate the HPA Axis in Male Rats and Mice: A Potential Role for Fibroblast Growth Factor-21

Abstract: In response to an acute threat to homeostasis or well-being, the hypothalamic-pituitary-adrenocortical (HPA) axis is engaged. A major outcome of this HPA axis activation is the mobilization of stored energy, to fuel an appropriate behavioral and/or physiological response to the perceived threat. Importantly, the extent of HPA axis activity is thought to be modulated by an individual's nutritional environment. In this study, we report that nutritional manipulations signaling a relative depletion of dietary carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 89 publications
2
24
0
Order By: Relevance
“…2D). High-fat diet was reported to enhance HPA axis activity (8,9), leading to hyperglycemic response to EPI (28). In this study, we further found that FAM132b gene therapy reduced serum levels of corticosterone, ACTH, norepinephrine (NE), and EPI ( Fig.…”
Section: Fam132b Gene Therapy Reduces Glycemic Response To Epi and Susupporting
confidence: 62%
See 1 more Smart Citation
“…2D). High-fat diet was reported to enhance HPA axis activity (8,9), leading to hyperglycemic response to EPI (28). In this study, we further found that FAM132b gene therapy reduced serum levels of corticosterone, ACTH, norepinephrine (NE), and EPI ( Fig.…”
Section: Fam132b Gene Therapy Reduces Glycemic Response To Epi and Susupporting
confidence: 62%
“…Thus, chronic stress is associated with a higher risk of type 2 diabetes (6), while regular exercise is helpful for glycemic control in the previous cohort studies (7). High-fat feeding not only causes glucose intolerance, insulin resistance and metabolic disorders, and also enhances HPA axis tone in a manner that resembles HPA hyperactivity in chronic stress exposure (8,9). Evidence from chronic stress suggests lowering glycemic response to HPA axis by some means contributes to glycemic control in patients with diabetes or hyperglycemia.…”
Section: Introductionmentioning
confidence: 99%
“…Mice fed a ketogenic diet (KD) show significant increase in FGF21 expression and serum levels [96,97,98] required for the activation of hepatic lipid oxidation, triglyceride clearance, and ketogenesis induced by KD [36]. However, unlike the murine model, in obese patients, a KD does not increase FGF21 serum levels [99] and even decreases its levels when a KD is combined with low calorie intake [100].…”
Section: Fgf21 and Carbohydratesmentioning
confidence: 99%
“…This may be explained by the increased BHB levels following dietary treatment. A recent study by Ryan et al found that the low carbohydrate and high fat ketogenic diet (KD) in male rats and mice resulted in an increase in hypothalamic-pituitary-adrenal (HPA) axis tone (25). Thus, we speculate that the increased activation of HPA axis associated with an absence of carbohydrates and increased levels of BHB may be associated with the observed behavioral changes in current study.…”
Section: Discussionmentioning
confidence: 99%